Food matters : a guide to conscious eating, with more than 75 recipes - Bittman, Mark (Simon & Schuster, 2009)
The "Minimalist" columnist and author of How to Cook Everything outlines an eating plan that is comprised of environmentally responsible choices, in a guide that shares insight into the risks associated with livestock production.